A new outcome measure for LUTS: Symptoms of Lower Urinary Tract Dysfunction Research Network Symptom Index‐29 (LURN SI‐29) questionnaire. Issue 6 (21st June 2019) - Cella, David; Smith, Abigail R.; Griffith, James W.; Flynn, Kathryn E.; Bradley, Catherine S.; Gillespie, Brenda W.; Kirkali, Ziya; Talaty, Pooja; Jelovsek, J. Eric; Helfand, Brian T.; Weinfurt, Kevin P.; ,
Abstract: Aims: To develop a representative, self‐report assessment of lower urinary tract symptoms (LUTS) for men and women, the symptoms of Lower Urinary Tract Dysfunction Research Network Symptom Index‐29 (LURN SI‐29). Methods: Women and men seeking treatment for LUTS at one of six academic medical centers in the US were assessed at baseline, 3‐month and 12‐month intervals. Twelve‐month data on 78 LURN SI‐29 items were analyzed among 353 women and 420 men using exploratory factor analysis (EFA), with factor structure confirmed using confirmatory factor analysis (CFA). Internal consistency, reliability, and validity of the five developed scales were evaluated by assessing correlations with the American Urological Association Symptom Index (AUA‐SI), the genitourinary pain index (GUPI), and the Pelvic Floor Distress Inventory‐20 (PFDI‐20), and by examining expected sex differences in scores. Results: EFA results (n = 150 women; 150 men) produced an interpretable eight‐factor solution, with three of the factors comprised of dichotomous items addressing LUTS‐associated sensations. The remaining five factors, confirmed with CFA in an independent sample of 473 participants, produced five scales: incontinence, urgency, voiding difficulty, bladder pain, and nocturia. Subscales and total LURN SI‐29 scores were correlated as expected with AUA‐SI, GUPI, and PFDI‐20. LURN SI‐29 scores also performed as expected in differentiating men from women based upon clinically expected differences, with men reporting more voiding difficulties and nocturia, and women reporting more urgency and incontinence. Conclusions: The LURN SI‐29 questionnaire has the potential to improve research and clinical outcome measurement for both men and women with LUTS.